The Role of Mathematics Teachers in Activating the Future Gate Tools in Public Schools in Jeddah Governorate - Alshmrani, Zahra Aun; Almalki, Abdulmalik Misfer (Journal of Educational and Psychological Sciences, 2020)
This research aims to acknowledge the Role of Mathematics Teachers in Activating the Future Gate Tools in Public Education Schools in Jeddah Governorate. The researchers used the experimental method and the questionnaire as a tool distributed to a random sample of (247) Mathematics teachers in public education schools in Jeddah Governorate using the Future Gate in the second semester of the school year 2019/2020. The SPSS was used to analyze the data where the following results were obtained: the entire questionnaire obtained a total average of (3.41 out of 5), rated as (great), and at the level of Domains the domain of activities and electronic educational tools obtained the highest average of (3.77) followed by the tool of the Virtual Classes at an average of (3.67) followed in the third place by the Electronic Tests at an average of (3.61) and all were rated as (great) score, and in the fourth place was the Electronic Content at an average of (3.37), and in the fifth place was the Discussions Circles at an average of (3.33) and in the sixth place was the Lessons Preparation Tool and the Detailed Plan at an average of (3.13) and finally was the Attendance Monitoring Tool at an average of (3.05) rated as medium score.Based on the results, the researchers have recommended to encourage the effective use of the Future Gate tools, with its multiple capabilities in educational aspect, and to develop the abilities of mathematics teachers in particular and the teachers of the Future Gate Schools in general in the educational and learning process.
Keywords: role; Mathematics Teachers; Learning Management Systems; Future Gate; Public Education School; Jeddah Governorate